Comparison of the composition and structure for coal-derived and petroleum heavy subfraction by an improved separation method. (15th May 2021) - Zhu, Yonghong; Tian, Feng; Liu, Yaqing; Cui, Louwei; Dan, Yong; Du, Chongpeng; Li, Dong
Highlights: An improved subfraction separation method was built for heavy oil. The subfraction composition and structure were comparatively studied. More reasonable molecular structures of heavy oil subfractions were obtained. Abstract: The property of coal-derived asphaltene and resin shows remarkable differences from petroleum one, such as the molecular aggregation and thermal cracking characteristics. It is significant to make deep-level analysis of their composition and structure to provide detailed molecule information for coal tar deep processing. In this paper, an improved separation method, which innovatively developed two-stage asphaltene extraction and two-stage silica gel separation coupling process, was built to obtain the purified asphaltene and resin components derived from coal tar (C-asp and C-res) and petroleum (P-asp and P-res). All samples were analyzed comparatively through Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), solid state cross polarization/magic angle spinning nuclear magnetic resonance spectroscopy ( 13 C-CP/MAS-NMR), thermogravimetric analysis (TG) and scanning electron microscopy (SEM). It is found that C-asp and C-res contain more OH groups resulting in stronger aggregate effect and OH-OH and OH-ether O are the main hydrogen bond. C-asp and C-res have more C-O of phenols and C = O of COOH group. C-asp and C-res have fewer and shorter alkyl side chains. The aromatic ring substitutive degree (σ) of C-asp and C-res is higher while the alkyl branching degree of P-asp and P-res is higher. Besides, asphaltene has higher σ, alkyl substituents number ( n ), average stack height of aromatic sheet ( Lc ), average number of aromatic sheets associated in per stacked cluster ( M ) and shorter average substituted alkyl chain length ( L ) compared with resin. Finally, the average molecular structure models of C-asp, P-asp, C-res and P-res are obtained.